1998
DOI: 10.1002/j.2048-7940.1998.tb01750.x
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of External Performance Measurement Tools in Program Evaluation

Abstract: Many rehabilitation hospitals use formal measurement tools to evaluate program performance. A potential advantage to using the Functional Independence Measure instrument through the Uniform Data System for Medical Rehabilitation (UDSMR) is that it provides information that allows an institution to compare its level of performance to those of other facilities. To assess whether joining UDSMR, along with an institution's continuous quality improvement efforts, could be associated with improved program performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Many of the studies reviewed lacked controls and failed to set adequate outcome criteria. [25][26][27][28][29] Most were little more than reports of student satisfaction. The small number of studies that did include control groups suggested that, under favorable circumstances, interactive learning methods did not conclusively improve students' perceptions of other health care disciplines.…”
Section: Outcome Studies and Curricular Development Literaturementioning
confidence: 99%
“…Many of the studies reviewed lacked controls and failed to set adequate outcome criteria. [25][26][27][28][29] Most were little more than reports of student satisfaction. The small number of studies that did include control groups suggested that, under favorable circumstances, interactive learning methods did not conclusively improve students' perceptions of other health care disciplines.…”
Section: Outcome Studies and Curricular Development Literaturementioning
confidence: 99%
“…In these studies, researchers evaluate applications for using program-based measurement and evaluation in different disciplines in the historical process. Another type of study in which the concepts of measurement and evaluation and program evaluation are a matter of research is studies that adopt the use of measurement and evaluation in program evaluation (Harmon et al, 1998;McDowell, 1992;Tusing & Breikjern, 2017). These studies include various measurement and evaluation approaches and methods researchers can employ in the program evaluation process.…”
Section: Measurement Evaluation and Program Evaluationmentioning
confidence: 99%